Cochrane Database of Systematic Reviews 2006
DOI: 10.1002/14651858.cd004918.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous shunts for glaucoma

Abstract: Background-Aqueous shunts are employed for intraocular pressure (IOP) control in primary and secondary glaucomas that fail medical, laser, and other surgical therapies. Objectives-This review compares aqueous shunts for IOP control and safety. Search strategy-We searched CENTRAL, MEDLINE, PubMed, EMBASE, NRR in January 2006, LILACS to February 2004 and reference lists of included trials. Selection criteria-We included all randomized and quasi-randomized trials in which one arm of the study involved shunts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 75 publications
0
31
0
3
Order By: Relevance
“…Glaucoma drainage devices or aqueous shunts, the preferred term used by the American National Standards Institute, were traditionally reserved for cases of refractory glaucoma where trabeculectomy had failed or was likely to fail 6. A growing experience of these devices has led to wider clinical indications, however, there is no current data on trends in their usage 6 7…”
Section: Introductionmentioning
confidence: 99%
“…Glaucoma drainage devices or aqueous shunts, the preferred term used by the American National Standards Institute, were traditionally reserved for cases of refractory glaucoma where trabeculectomy had failed or was likely to fail 6. A growing experience of these devices has led to wider clinical indications, however, there is no current data on trends in their usage 6 7…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have reported 40–90% success rate with trabeculectomy in OAG 2 3 4 5 6. However, the majority of the studies with GDD include patients with neovascular, uveitic, developmental and mixed glaucoma (referred to as refractory, intractable or complicated glaucoma) 7 8 9 10 11 12 13 14 15 16 17. Furthermore, there are fewer studies comparing the two surgical modalities, and only one of them is in patients with OAG.…”
mentioning
confidence: 99%
“…Surgeons may use a tube without a reservoir (for example, Ex-PRESS) or a space-holder or reservoir to enhance aqueous humor outflow or to modify healing (for example, Ologen) and to promote continued drainage from the anterior chamber through a standard partial thickness scleral flap used in a standard trabeculectomy. Another technique, a device composed of both a silicone tube and an explant plate, called an aqueous shunt, is also a surgical option to treat glaucoma, but this technique is not within the scope of this review (Minckler 2006). …”
Section: Introductionmentioning
confidence: 99%